Effect of crop maturity condition and operating factors on the threshing performance of wheat thresher - Ali, Muhammad Mohsin; Shahzad Noor, Rana; Hussain, Fiaz; Khan, Hassan Farid; Shah, Anis Ali; Shah, Adnan Noor (Journal of Pure and Applied Agriculture, 2024)
Sustainable agriculture is majorly related to mechanized agriculture systems. The outdated threshing operations lead to a negative impact on wheat threshing performance and contribute to overall post-harvest losses. Mechanized agriculture could produce encouraging results for productivity enhancement including grain damage reduction, better efficiency, and improved threshing technology. The objective of this research study was to assess the effect field operating conditions in the farmers field and maturity characteristics of wheat on threshing performance of locally developed wheat thresher during wheat seasons 2017-18. The wheat thresher produced significantly higher results for wheat (Faisalabad-2008) with the mean threshing efficiency (98.83%) and grain cleaning efficiency (98.93%) at crop moisture (16.6%) and feeding of 52 kg/min. while the least grain breakage percentage (0.75%) was found. The quantity of grain lost in wheat straw was found to be minimum 0.16% at the feeding rate of 47 kg/min and mid harvesting stage (16.6%). The wheat thresher chopped straw size was (2.28 cm) accurate and uniform at moisture content 16.6% (mid harvesting stage) while the straw chopping was non-uniform and irregular at late harvesting stage of wheat crop (1.93cm). The maximum fuel consumption and energy utilized were calculated to be 6.71 L/h and 76.57 kWh respectively for wheat variety Lasani-2008 (V3) at feeding rate FR3, 52 kg/min. The results revealed that the crop moisture content and feeding rate has significant effects on threshing efficiency, cleaning efficiency and grain damage.